Penyuluhan Berbasis Nilai-Nilai Tri Hita Karana Untuk Meningkatkan Moderasi Beragama Umat Hindu Di Kota Mataram - Ni Wayan Rasmini; I Wayan Karta (IAHN Gde Pudja Mataram, 2022)
This community service activity aims to improve understanding, attitudes and skills about the values ​​of tri hita karana in optimizing the religious moderation of Hindus in Sekarbela District, Mataram City. There were 24 target audiences, 6 each from Banjar Tri Parartha, Batu Dawa, Dangi Tukad and Batu Ringgit administrators. The place of activity is focused on the Saraswati Tanjungkarang Permai Temple. The activity is divided into 2 stages, stage 1 is outreach activities with direct learning methods to instill the concept of implementing the tri hita karana values. Phase 2 is a simulation of the implementation of the Tri Hita Karana aspects, with 2 groups in each aspect, to develop knowledge, attitudes and skills of religious moderation. The simulation of the paluhuran aspect is carried out with the theme of making ceremonial facilities, and the implementation of the god yadnya ceremony. The simulation on the pawongan aspect has the theme of mutual cooperation in public places and Banjar meetings. The simulation of palemahan aspects of the theme is burial/burning of bodies and cleaning/preservation of the environment. Data from counseling and simulation results were collected using a 4-scale observation guide instrument with religious moderation indicators. Data analysis was carried out in a qualitative descriptive manner. The results of service activities in the form of understanding, attitudes and behavior of religious moderation reached an average of 77.7% which was classified as good. In the aspect of human relations with God, religious moderation is in the very good category. Aspects of human-human relations, in the good category. In the aspect of human-nature relations in the good category. Successively the most superior achievement of religious moderation occurred in the paluhuran aspect followed by the pawongan and palemahan aspects. It is hoped that every believer has proper knowledge of attitudes and skills about tri hita karana so that they can carry out good religious moderation.